STEAM education in preschool education: We design our school for our visually impaired friend. (3rd April 2022) - Hacıoğlu, Yasemin; Suiçmez, Esra
Abstract: Integration of STEAM disciplines in preschool education is considered to be difficult for children to work as engineers and perform robotics applications. Therefore, preschool STEAM activities are needed. The study aims to convey how to implement the preschool STEAM activity named "We design our school for our visually impaired friend" with children aged 48–66 months. Children ran -engineering, technology, and artistic- design processes by scientific and mathematical inquiry. They worked for a week under the guidance of their teacher. First, they designed tactile paths for the visually impaired person in their school, tested with dramatic inquiry, and presented. Second, they coded and tested Bee-Bot to help guide and accompany their disabled friend. Then, they designed posters for awareness of the life of impaired people and evaluated them. Then they hung it on the walls of the school and explained the importance of roads for the visually impaired, tasks of Bee-Bot to other children, teachers, and parents. They evaluated each other and themselves while testing their designs and used scientific concepts – the importance of seeing sense organs, mathematical shapes. The children had fun and learned by working cooperatively throughout the activity for the process of STEAM activity.